Kafka's Writing Machine: Metamorphosis in the Penal Colony - Arnold Weinstein (Studies in 20th & 21st Century Literature, 1982)
Kafka's "In the Penal Colony" is a problematic story, largely because of the conflicting interpretations it has received: does its famous machine dispense grace or torture? Is Kafka giving us a parable of Old vs. New Law? How does the "liberal" explorer or the "liberal" reader assess the Officer's impassioned pleading for the Machine and the kind of justice it serves? A strange kind of coherence emerges, however, when one focusses on the central unifying motif of the story: understanding. The tale itself is little more than the Officer's desperate effort to make the explorer-reader understand; the machine itself makes its victim understand the nature of justice. Language is, of course, a primary vehicle for understanding, and Kafka's story dramatizes two radically opposed languages: verbal and physical. All efforts to bridge the distance between people, between matter and spirit, seem to fail, at least insofar as spoken language is concerned; the machine's mission is to create physical language, an unmediated script which is the reality of which it speaks. By writing the crime onto and into the flesh of the criminal, the machine offers a sublime and frightening figure of "visceral knowledge," of the open self as the opened self. By entering into the machine himself, the Officer undergoes the classic Kafka metamorphosis: he becomes the prisoner, and he thereby suffers knowledge. The entire parable may be seen as an illustration of the writer's yearning for a language so potent that the reader would experience, "in the flesh," the writer's words. Kafka's own narrative techniques aim at precisely such a metamorphosis in the reader.
Keywords: In the Penal Colony; In der Strafkolonie; understanding; motif; meaning; Language; verbal; physical; spoken language; metamorphosis